Problematika Guru Sejarah Kebudayaan Islam dalam Penerapan Media Pembelajaran Di MTs Negeri 2 Surakarta - Priyangga Nur Oktaviola; Hafidz Hafidz (STAI Terpadu Yogyakarta, 2024)
This research investigates the problems faced by Islamic cultural history teachers in implementing learning media at MTs Negeri 2 Surakarta. Learning media has an important role in increasing the effectiveness of learning the history of Islamic culture. However, this research identified several problems faced by teachers in the development and use of learning media. This research uses qualitative research methods and relies on sources such as scientific journals, scientific articles, and interviews related to this issue. The results of the research identified several main problems, including a lack of teacher skills in developing and utilizing learning media that is appropriate to learning objectives, a lack of understanding of the various types of media that can be used, limited knowledge about the use of technology in learning, and a lack of creativity and innovation in the use of media for learning. learning the history of Islamic culture.This study provides an important understanding of the role of learning media in learning the history of Islamic culture and proposes solutions to overcome the problems identified. Solutions include teacher training and development, increased creativity and innovation, better resources and references, more effective use of technology, mentoring, collaboration, evaluation, and feedback. By implementing these steps, it is hoped that Islamic cultural history teachers can improve the quality of their learning through the use of more effective learning media.